Pemberdayaan Masyarakat Oleh Mahasiswa Melalui Budidaya Dan Pelatihan Pengolahan Tanaman Obat Keluarga (TOGA) Dengan Memanfaatkan Lahan Perkarangan Menuju Keluarga Sehat Di Gampong Lam Bheu Kabupaten Aceh Besar - Mujiburrahmad; Elly Kesumawati; Sri Fitri (Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
Most of the houses owned by the community in Gampong Lam Bheu have yards and have not been used. The main problems of partners are: (1) Lack of knowledge and skills in TOGA cultivation starting from land preparation, seeding, planting and care. (2) Do not know what types of plants are included in TOGA (3). Lack of knowledge and skills in processing TOGA into herbs and other herbal medicines. (4). There is no village-owned TOGA educational park yet. Implementation activities will begin with the coordination and socialization stage, then continue with counseling on the introduction of types, benefits of family medicinal plants and making brochures. The next activity was a demonstration of the use of yards, proper cultivation of plants starting from cultivating the land, seeding, planting and maintenance, production of liquid organic fertilizers with household waste as raw materials and production of vegetable pesticides. Followed by a demonstration of the processing of TOGA into herbal medicine and herbal medicines, partners will then be facilitated in making the Village's Educational Park. Conclusion This PMM activity program is proven to have: Increased knowledge, skills and ability to understand the types and benefits of family medicinal plants, ability to understand TOGA cultivation, production of liquid organic fertilizer, and production of vegetable pesticides, as well as ability to process family medicinal plants into herbs and medicines herbal medicines that have high selling value